2000
DOI: 10.1148/radiology.214.2.r00fe45467
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Switch Procedure for D-Transposition of the Great Arteries: Quantitative Midterm Evaluation of Hemodynamic Changes with Cine MR Imaging and Phase-Shift Velocity Mapping—Initial Experience

Abstract: The anatomic situation after arterial switch repair tended to produce temporary stenoses in the primary pulmonary arterial branches, with significant changes in hemodynamics. These changes may affect the long-term outcome and go undetected with other imaging modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 36 publications
2
41
0
1
Order By: Relevance
“…Both in vitro and in situ studies 21 have demonstrated close agreement between Doppler sonography, cardiac catheterization, and VEC MRI for quantification of vascular stenosis. It will be important to determine in future studies whether monitoring of flow through different stents can be used to detect and quantify stent stenosis.…”
Section: Discussionmentioning
confidence: 80%
“…Both in vitro and in situ studies 21 have demonstrated close agreement between Doppler sonography, cardiac catheterization, and VEC MRI for quantification of vascular stenosis. It will be important to determine in future studies whether monitoring of flow through different stents can be used to detect and quantify stent stenosis.…”
Section: Discussionmentioning
confidence: 80%
“…(27,28) Gd-MRA is used to visualize the 3D anatomy, particularly the relationship between the pulmonary arteries and the aorta, while spin-echo sequences are used to accurately assess sites of stenoses. It has been shown that this combination of techniques is superior to echocardiography and compares favorably with conventional X-ray angiography in detecting signifi cant lesions.…”
Section: Tetralogy Of Fallotmentioning
confidence: 99%
“…(28) A less common complication of the arterial switch procedure is coronary stenosis secondary to the reimplantation procedure. Although X-ray angiography represents the modality of choice, coronary MR angiography is particularly useful when assessing the proximal coronary arteries.…”
Section: Tetralogy Of Fallotmentioning
confidence: 99%
“…After the Lecompte maneuver, not only flattened anterior MPA (low-pressure), branch PA stenosis, and supravalvular PS at pulmonary bifurcation can occur as a consequence of posterior compression of MPA by the ascending aorta (Williams et al, 1997;Gutberlet et al, 2000); but also the aorta itself (systemic-pressure) may be compromised. Therfore, aortic neocaorctation was reported (Muster et al, 1987;Serraf et al, 1995).…”
Section: Commentmentioning
confidence: 99%